Cognitive disorders and fitness of the elderly in residential homes in Bydgoszcz - Podhorecka, Marta; Turska, Anna; Gębka, Dominika; Perkowski, Radosław; Perkowska, Joanna; Jaroch, Alina; Nicpoń-Nożewska, Klara; Radzińska, Michalina; Grzanka-Tykwińska, Anna; Zukow, Walery; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2017)
<span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Introduction.<span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> Process of ageing and the growing number of people in retirement age is one of the main problems of the modern world. Together with advancing age both fitness and mental capacity deteriorate. Research proves that there is dependence between cognitive functions and fitness of the elderly. <span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Aim.<span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> The aim of the study was to compare fitness with cognitive functions among residents of residential home in Bydgoszcz. <span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Material and methods. 59 people (35 women and 24 men) at the age of 60 to 98 participated in the study. Mini-Mental State Examination (MMSE) was used to assess cognitive functions. Fitness was assessed by means of Tinetti Test. The subjects were divided according to a) age: group 60-75 and 75+ and b) gender. <span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Results.<span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> Negative correlation was observed between age and Tinetti Test results. In the study there was positive and moderate correlation between MMSE scale and Tinetti Test results. In Tinetti Test results regarding differences due to gender were close to statistical significance. <span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Conclusions.<span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> There is a dependence between age and weakening of fitness in the elderly in residential homes in Bydgoszcz. Risk of falls increases with age. There is a dependence between cognitive functions disorders and fitness of the elderly from residential homes in Bydgoszcz.